Fetal Hemodynamic Responses to Arterial Occlusion of Acardiac Twins. (28th August 2021) - Traisrisilp, Kuntharee; Luewan, Suchaya; Tongprasert, Fuanglada; Srisupundit, Kasemsri; Tongsong, Theera
Abstract: The objective of this study was to comprehensively assess fetal hemodynamic adaptions to occlusive procedures. Twin pregnancies complicated with acardiac twin and hydrops fetalis of the pump twin were recruited. The occlusive procedures — either alcoholization, radiofrequency ablation, coil embolization or occlusive glue — were performed under ultrasound guidance. Various hemodynamic parameters were assessed before, shortly after, then every 6 h for 48 h and 2−4 weeks after the procedures. Seven pregnancies were recruited. The median (range) gestational age of intervention was 21 (17−26) weeks of gestation. Before the procedures, all cases showed normal cardiac function. Just after the procedures, all cases showed an increase in Tei index and isovolumic relaxation time but returned to preocclusion levels within 6−48 h, except for two cases that were persistently high. Increased preload and poor shortening fraction were observed in two cases, leading to heart failure, with one recovery and one death in utero. Five out of the seven cases got through the critical period with a gradual return to normal hemodynamics, ending with the disappearance of hydrops and successful outcomes. It was concluded that the occlusive procedure could aggravate the overworked heart, leading to heart failure. Preocclusion preload index and Tei index may predict risk of heart failure due to the occlusion. This small series strongly suggests that the occlusion should be performed before the deterioration of cardiac function.